Goal Management Training and Computerized Cognitive Training in Depression—a 2-Year Follow-Up of a Randomized Controlled Trial - Hagen, Bjørn Ingulfsvann; Stubberud, Jan (Frontiers in Psychiatry, 2021)
Objective: Information on the long-term effects of cognitive remediation (CR) in major depressive disorder (MDD) is lacking. The present study reports two-year follow-up data from a previously published randomized controlled trial (RCT) from our research group, comparing Goal Management Training (GMT), a strategy-based CR intervention, to drill-and-practice computerized cognitive training (CCT). In previous work, we found comparable improvements in executive function (EF), in addition to reductions in depressive symptoms, following both GMT and CCT at six-month follow-up. Methods: Forty-two participants of the RCT, all diagnosed with MDD, were invited to complete rating-scales pertaining daily-life EF, rumination, and depressive symptoms. Explorative analyses compared the two-year follow-up with previously published baseline and six-month follow-up data, using nonparametric statistics. Similarly, GMT and CCT were compared at the two-year follow-up, and completers were compared with noncompleters. Results: Twenty participants completed the study. Overall, completers (n = 20) and noncompleters (n = 22) were similar. There were no significant differences between GMT (n = 11) and CCT (n = 9) for any outcome two years post-treatment. Reduction compared to baseline in depressive symptoms and rumination, but not in daily-life EFs, emerged for GMT only. Conclusions: Findings suggest long-term improvements in mental health following GMT, while improvements in everyday EFs might require additional treatment or maintenance to sustain. Caution is warranted in the interpretation due to the small sample size and high attrition rates.